Why the rich are nastier than the poor: A note on optimal punishment - Steffen Huck; Wieland Müller (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1998)
Studying evolutionarily successful behavior we show in a general framework that when individuals maximizing payoff differentials invest resources in punishing others. Interestingly, these investments are increasing in individuals, own wealth and decreasing in the wealth of others.
urn:nbn:de:kobv:11-10056426
Keywords: 330